Family analysis and literature study of hereditary hypophosphatemic rickets with hypercalciuria - Lufeng Wang; Gulimire Kulaixi; Jiazireya Zaiyinati; Guzhalikezi Aibai; Danyang Du; Yanying Guo (BMC, 2024)
Abstract Background Hereditary hypophosphatemia rickets with hypercalciuria (HHRH) is a rare autosomal recessive disorder characterised by reduced renal phosphate reabsorption leading to hypophosphataemia, rickets and bone pain. Here, we present a case of HHRH in a Chinese boy. Case presentation We report a 11-year-old female proband, who was admitted to our hospital with bilateral genuvarum deformity and short stature. Computed Tomography (CT) showed kidney stones, blood tests showed hypophosphatemia, For a clear diagnosis, we employed high-throughput sequencing technology to screen for variants. Our gene sequencing approach encompassed whole exome sequencing, detection of exon and intron junction regions, and examination of a 20 bp region of adjacent introns. Flanking sequences are defined as ±50 bp upstream and downstream of the 5' and 3' ends of the coding region.The raw sequence data were compared to the known gene sequence data in publicly available sequence data bases using Burrows-Wheeler Aligner software (BWA, 0.7.12-r1039), and the pathogenic variant sites were annotated using Annovar. Subsequently, the suspected pathogenic variants were classified according to ACMG's gene variation classification system. Simultaneously, unreported or clinically ambiguous pathogenic variants were predicted and annotated based on population databases. Any suspected pathogenic variants identified through this analysis were then validated using Sanger sequencing technology. At last, the proband and her affected sister carried pathogenic homozygous variant in the geneSLC34A3(exon 13, c.1402C > T; p.R468W). Their parents were both heterozygous carriers of the variant. Genetic testing revealed that the patient has anLRP5(exon 18, c.3917C > T; p.A1306V) variant of Uncertain significance, which is a rare homozygous variant. Conclusion This case report aims to raise awareness of the presenting characteristics of HHRH. The paper describes a unique case involving variants in both theSLC34A3andLRP5genes, which are inherited in an autosomal recessive manner. This combination of gene variants has not been previously reported in the literature. It is uncertain whether the presence of these two mutated genes in the same individual will result in more severe clinical symptoms. This report shows that an accurate diagnosis is critical, and with early diagnosis and correct treatment, patients will have a better prognosis.